PENGARUH PENAMBAHAN KAPUR SEBAGAI BAHAN STABILISASI TANAH DITINJAU DARI NILAI CBR (CALIFORNIA BEARING RATIO) - Masta'in, Masta'in (SIMETRIS, 2023)
Soil is the basic foundation of a building that stands on it, soil properties such as relatively small soil carrying capacity and so on can cause damage to some of the construction on it. The addition of lime in this research aims to repair damaged soil on the Menden-Sumber Road. The purpose of this study was to determine the effect of lime addition on the CBR value. The results of this study indicate that mixing lime in the soil can increase the CBR value. Variations in lime mixing are 0%, 2.5%, 5%, 7.5%, and 10% of the dry weight of the soil. The CBR values for mixing 0% and 2.5% lime were 43% and 50%, while those for mixing lime 5%, 7.5% and 10% were 66.33%, 64% and 61%. The effect of adding lime to the CBR value gives a significant effect, especially to the addition of 5% lime, which is equal to 66.33%.